The effect of reward and punishment on work loyalty on IBC Telkomsel in Bandung City - Taruna, Indra; Tarmidi, Didi; Amalia, Shendy; Marinda, Vina Silviani (Jurnal Mantik, 2024)
This research aims to find out the influence of Reward and Punishment on Work Loyalty at IBC Telkomsel in Bandung City. This research includes quantitative descriptive research, with multiple linear regression analysis approaches that use a brushioner research instrument. The sample in this study was Telkomsel IBC employees in Bandung City which amounted to 134 respondents who were analyzed with the SPSS program version 25. The results of this study found that rewards have a significant effect on work loyalty, evidenced by the value of thitung significance greater than table and with a large enough coefficient value so that the reward affects work loyalty. Punishment also has a significant effect on work loyalty, evidenced by the value of thitung significance greater than ttabel and with a fairly large value of coefiesen, so punishment also affects work loyalty. In multiple linear analyses it is known that reward has a greater influence on work loyalty compared to the punishment variable.